Grosse Kunstausstellung München 1984. (München : Haus der Kunst, 1984)
Bittner, Eva Maria ; Casagrande, Peter ; Goektke, Karlheinz ; Hentschel, Claus Dietrich ; Nagel, Peter ; Müller, Eugen Wilfried ; Schneider, Josef ; Thiele, Peter ; Winzens, Dorit ; Zimnik, Rainer ; etc.
Grosse Kunstausstellung München 1984, Haus der Kunst, München, 30. Juni bis 16. September 1984
boek
Keywords: München